2012
DOI: 10.1016/j.bpj.2011.11.2130
|View full text |Cite
|
Sign up to set email alerts
|

Nmr Structural Studies of Antimicrobial Peptides, LPcin

Abstract: 1Z profiles followed a theoretical square-law functional dependence [4]. Our preliminary results show that R 2 CP is sensitive to hydration levels as well as the acyl position, thus indicating the presence of slow dynamic modes. The R 2 CP rates of the acyl segments near the polar head groups increase with lipid dehydration, while the acyl segments deeper in the hydrophobic region show lower R 2 CP values at high dehydration levels. Similar studies in presence of peptides and proteins can give insight into opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been reported that this small cationic peptide has antibacterial activity against both Grampositive and Gram-negative bacteria (4,5). The correlation between the structure and the antimicrobial activity of this peptide was previously studied in detail by means of solution and solid-state NMR spectroscopies (6)(7)(8)(9)(10). As part of our efforts to find novel AMPs with better antimicrobial activity than LPcin, we designed 11 LPcin analog peptides and chose three analog peptides that showed the best antibacterial activ-ity, using the agar hole test against five pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that this small cationic peptide has antibacterial activity against both Grampositive and Gram-negative bacteria (4,5). The correlation between the structure and the antimicrobial activity of this peptide was previously studied in detail by means of solution and solid-state NMR spectroscopies (6)(7)(8)(9)(10). As part of our efforts to find novel AMPs with better antimicrobial activity than LPcin, we designed 11 LPcin analog peptides and chose three analog peptides that showed the best antibacterial activ-ity, using the agar hole test against five pathogens.…”
Section: Introductionmentioning
confidence: 99%